Implementation of Inquiry Learning Method in Maharah al-Qiro'ah - Shalihah, Siti; Nisa, Ummi; Yani, Achmad (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
Inquiry learning is a strategy student-centered learning as the subject of learning itself in Arabic subjects, especially reading skills (maharah al-qiro'ah. The students expectedly are able to read correctly and understand the content of the reading. In Arabic learning, there are four maharah (skills), including maharah al-qiro'ah, maharah al-kalam, maharah al-kitabah, maharah al-istima'. In this article, maharah al-qiro'ah was discussed, which focused on reading skills and also text understanding. Primary data sources in this research included interviews with teachers or instructors involved in maharah al-qira'ah using the inquiry method. Secondary data sources in this research encompassed books and literature related to maharah al-qira'ah learning and the inquiry method, scientific journals discussing the inquiry-based learning strategy in the context of Arabic language learning. Semi-structured interviews was involved in data collection techniques with teachers and learners, direct observation to document learning practices in the classroom and document analysis. Data analysis techniques used in this research included transcription of interviews and observation notes. The results showed that Inquiry learning was able to make the students active and think critically and independently. This research provided insights into the exploration and adaptation of the Inquiry learning method for Maharah al-Qiro'ah, offering a structured approach for teachers to enhance students' reading skills and comprehension, thus facilitating their ability to extract the main ideas from what they read. Additionally, this article emphasized the importance of methodological diversity in teaching, which can enhance student engagement and lead to better learning outcomes.